Minimization of Risks During the Liquidation of Emergencies Consequences - Shtukin, M. V.; Kuzyomin, A. Ya.; Sirodzha, I. B. (Інститут проблем реєстрації інформації НАН України, 2013)
It has been developed a decision for making methodology of the liquidation of emergencies consequences with the help of intelligent decision-making systems based on micro situation quantum knowledgebase of precedents. Fig.: 1. Refs: 3 titles.